Speech restrictions and linguistic disorders: A study of the novels of Jat Dost in the light of psycholinguistics - Saeed, Roaa; Mahmoud , Ahmed (Al-Adab Journal, 2025)
This research aims to shed light on the impact of linguistic prohibitions and speech disorders on humans by studying Jean Dost’s novels in the light of psycholinguistics. Speech prohibitions and linguistic disorders have an impact on human behavior, whether on the external, motor and physical level or on the internal level (feelings and sensations). These prohibitions are in the process of communication and delivering the message, and what can be clarified in communication and explained despite the presence of the obstacle of prohibitions in conveying the complete message. Communication does not depend on language alone, but on other matters that contribute to the process of building trust between the two parties of communication (sender/receiver) and thus the success of the communication process. If there are prohibitions or disturbances in speech, the communication process needs careful review and consideration in order to reach a goal. The message clearly.